2013
DOI: 10.1186/1475-2840-12-77
|View full text |Cite
|
Sign up to set email alerts
|

Association between non-alcoholic fatty pancreatic disease (nafpd) and the metabolic syndrome: case–control retrospective study

Abstract: BackgroundFatty liver is associated with insulin resistance, dyslipidemia, and obesity and is therefore considered a phenotype of metabolic syndrome. However, less is known regarding the metabolic abnormalities associated with non-alcoholic fatty pancreatic disease (NAFPD; fatty pancreas). The present study was performed to ascertain whether fatty pancreas is associated with specific metabolic risk factors and with metabolic syndrome as defined by the Adult Treatment Panel III.MethodsFive-hundred-fifty-seven h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
100
1
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(131 citation statements)
references
References 28 publications
8
100
1
13
Order By: Relevance
“…In 2013, Wu and Wang et al 23 confirmed an association between the occurrence of fatty pancreas and metabolic risk factors. Results suggested that older age, greater BMI, increased abdominal waist circumference and metabolic variables (glycated haemoglobin, lipid parameters and systolic blood pressure) were associated with NAFPD 23…”
Section: Nafpd and Metabolic Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2013, Wu and Wang et al 23 confirmed an association between the occurrence of fatty pancreas and metabolic risk factors. Results suggested that older age, greater BMI, increased abdominal waist circumference and metabolic variables (glycated haemoglobin, lipid parameters and systolic blood pressure) were associated with NAFPD 23…”
Section: Nafpd and Metabolic Riskmentioning
confidence: 99%
“…The central factor bringing these conditions together is the metabolic syndrome, diagnosis of which is based on the National Cholesterol Education Program Adult Treatment Panel III when three or more of the following criteria are present: abdominal obesity (waist circumference ≥90 cm for males or ≥80 cm for females), increased triglyceride concentration (≥150 mg/dL), decreased high-density lipoprotein cholesterol (HDL-C) (<40 mg/dL for males or <50 mg/dL for females), hypertension (systolic blood pressure ≥130 mm Hg and diastolic blood pressure ≥85 mm Hg) and elevated fasting blood glucose concentration (≥110 mg/dL) 23. Therefore, it should go without saying that every patient with metabolic syndrome should undergo evaluation for both NAFLD and NAFPD.…”
Section: Nafpd and Metabolic Riskmentioning
confidence: 99%
“…Obesity also leads to the infiltration of fat in organs such as heart, kidneys, liver and pancreas [10]. Wu et al found that fatty pancreas is strongly associated with specific parameters of metabolic syndrome such as obesity, increased fasting blood glucose, elevated HbA1c and dyslipidemia [33]. It can be implied that NAFPD may represent a meaningful manifestation of metabolic syndrome.…”
Section: Clinical Consequencesmentioning
confidence: 99%
“…A previous study has reported the strong association between fatty liver disease and metabolic relevance is high previous study [4]. Non-alcoholic fatty liver was also shown to predict the occurrence of cardiovascular disease, such as dyslipidemia, abdominal obesity, and metabolic syndrome [5]. An increase of fat deposition in pancreas as well as liver appeared as an HE abnormality in several clinical index values.…”
mentioning
confidence: 99%